(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aimed to assess knowledge, risk awareness, and preventive and coping skills related to sexual abuse among primary school students in Hanoi, Vietnam. Methods: A cross-sectional study was conducted among 430 students from grades 3 to 5 at 4 public primary schools in Hanoi during the 2024-2025 academic year. Data were collected using a structured self-administered questionnaire covering demographic characteristics, awareness of sexual abuse risks, and preventive and coping skills. Descriptive statistics were used for data analysis. Results: Most students reported prior exposure to basic personal safety education, including body autonomy and seeking help (82.5%). However, correct awareness of common risk behaviors remained limited, ranging from 30.8-41.8%. Students were more likely to recognize direct grooming behaviors such as gift-giving (82.9%) than psychological manipulation tactics, including requests for secrecy (63.4%). In contrast, preventive and coping skills were well recognized, with over 90% of students identifying appropriate responses such as refusing unwanted contact, leaving unsafe situations, calling for help, and reporting to trusted adults. Conclusions: Primary school students have a good understanding of prevention and response skills when faced with the risk of sexual abuse, but there remains a significant gap in risk awareness and identification of abusive tactics. This highlights the need to strengthen structured, age-appropriate sexual abuse prevention education programs in the school environment.